1993
DOI: 10.1046/j.1469-0705.1993.03040284.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Eagle—Barrett (prune belly) syndrome and a thickened, poorly functional bladder wall after early second‐trimester decompression of feta1 megacystis

Abstract: The management of bladder outlet obstruction in the fetus remains a debated issue. Recent data suggest the use of cystocentesis for the possible relief of the bladder neck obstruction or for the opening of posterior urethral valves. This case report adds further support for the use of cystocentesis and observation prior to the placement of an indwelling bladder shunt. The case further demonstrates that relief of the megacystis may not prevent prune belly syndrome, bladder dysfunction or renal damage. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Case reports and small series have demonstrated that renal function cannot be predicted by fixed cut-offs of urine analysis alone. [4] [5], [6] [7]. Recent reports emphasise that besides urine electrolytes, osmolarity and beta-2-microglobuline renal sonomorphology and amount of amniotic fluid may be predictors for postnatal renal function [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Case reports and small series have demonstrated that renal function cannot be predicted by fixed cut-offs of urine analysis alone. [4] [5], [6] [7]. Recent reports emphasise that besides urine electrolytes, osmolarity and beta-2-microglobuline renal sonomorphology and amount of amniotic fluid may be predictors for postnatal renal function [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%